Structurally similar mixed-valent coordination compounds formed during the interaction of bis-5-pyridylmethylene-2-thioimidazolone with CuBr2 и CuCl2. (1st October 2022) - Finko, Alexander V.; Guk, Dmitry A.; Saakian, Arevik S.; Moiseeva, Anna A.; Tafeenko, Viktor A.; Shiryaeva, Ekaterina S.; Pergushov, Vladimir I.; Melnikov, Mikhail Ya; Komlev, Aleksei S.; Beloglazkin, Andrei A.; Borisov, Roman S.; Zyk, Nikolai V.; et al.
Graphical abstract: Abstract: A novel mixed-valent binuclear copper (I/II) coordination compound was obtained by interaction of (5Z, 5′Z)-2, 2′-(ethane-1, 2-diylbis(sulfanediyl))bis(3-allyl-5-(pyridin-2-ylmethylene)-3, 5-dihydro-4H-imidazol-4-one) with CuBr2 in n -BuOH. A structural comparison of this compound with a similar complex obtained in the reaction of the same ligand with CuCl2 shows that the complex structure-determining role belongs primarily to the ligand rather than the anion of the initial inorganic salt.